A high-safety electrolyte based on functionalized ionic liquid and polyurethane for lithium batteries. (1st December 2022) - Fang, Li; Sun, Wang; Hou, Wenshuo; Wang, Zhenhua; Sun, Kening
Highlights: A heat-resistant and non-flammable electrolyte is prepared by introducing Pyr12O1 FSI (IL1) to PU matrix. PU-IL1 electrolyte exhibits a high ionic conductivity of 0.29 mS cm −1 at room temperature. The superiority of IL1 and synergy between IL1 and PU are investigated. PU-IL1 electrolyte endows LFP/Li batteries with high performance at 30 °C and 80 °C. Abstract: Developing high-safety electrolytes is very important to improve the safety and operative temperature of lithium batteries. In this study, a heat-resistant and non-flammable electrolyte is constructed by introducing a functionalized ionic liquid N-methyl-N-methoxyethyl-pyrrolidinium bis(fluorosulfonyl)imide (Pyr12O1 FSI, IL1) into porous polyurethane (PU) matrix. IL1 contains ether functional group, which can increase the chain flexibility of IL and provide more ion migration channels. Moreover, IL1 shows high compatibility with PU matrix because the intermolecular hydrogen bond is formed by NH groups of PU and ether oxygen of IL1, which is evidenced by Fourier transform infrared spectroscopy (FTIR) tests and density functional theory (DFT) calculations. The binding energy further corroborates the enhanced intermolecular interaction between IL1 and PU. Owing to the superior characteristics of IL1 and synergetic coupling with PU, PU-IL1 electrolyte exhibits good electrochemical performance and endows LiFePO4 /Li (LFP/Li) battery with a high specific capacity of 135 mA h g −1 and 99% capacity retention after 100 cycles at 0.2C, 30 °C. In addition, the LFP/Li battery with PU-IL1 electrolyte exhibits a high capacity of 134 mA h g −1 (0.5C) and it remains 98% after 100 cycles at a high temperature of 80 °C.